TOP OF THE MOST FAMOUS ANCIENT CITIES OF CENTRAL ASIA - Teshaboyeva Nafisa Zubaydulla qizi; Safarova Oydinoy Azizbek qizi (TADQIQOTLAR.UZ, 2024)
Annotation: Uzbekistan, a landlocked gem in Central Asia, is a treasure trove of ancient wonders, where the echoes of history reverberate through its majestic landscapes and architectural marvels. From the bustling markets of Tashkent to the legendary Silk Road cities of Samarkand, Bukhara, and Khiva, Uzbekistan offers a journey through time, where the past intertwines seamlessly with the present. At the heart of Uzbekistan's allure lies its rich historical legacy, shaped by a convergence of cultures, religions, and empires. Traversed by the fabled Silk Road, Uzbekistan served as a crossroads of civilizations, where merchants, scholars, and conquerors left indelible marks on its cultural landscape. The remnants of these interactions are evident in the diverse architectural styles, intricate artwork, and vibrant traditions that characterize the region.